A educação de jovens e adultos digital: estudo de caso de uma metodologia como possibilidade emancipadora. - Monteiro, Ligia Di Bella Costa (2014)
This article has as subject the ""Youth and Adults Education"" - known as EJA in Portuguese and intends to answer the main question: ""What are the difficulties and contributions of EJA - Digital for the graduation of youth and adults at middle school?"". During the investigation of epistemological principles and elements of the proposed question we searched for articles developed by Freire (1978; 2011a, 2011b, 2011c, 2011), Gadotti & Romão (2011), Gadotti (1996), Jeffrey & Aguilar (2012), Di Pierro, Joia & Ribeiro (2001), Beigesel (1974), Mayo (2004), Franco (2011) and others. This way, we tried to understand the researched subject (the EJA project). Since the EJA - Digital project is considered a new propose of education (it has began experimentally in the second semester of 2006), the best research methodology found was the case study, which the main feature is to deeply explore current facts. For the methodological foundation, we based it on Yin (2001) researches, and to adapt it to the specificities of education we used André (2005) researches. The case study enables the use of some instruments for the data collection in this research. The overall goal of this article is to understand the possibilities of pedagogical practice of EJA Digital contributions to the youth and adults education.